2008
DOI: 10.1111/j.1365-2923.2001.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Training physicians in communication skills with adolescents using teenage actors as simulated patients

Abstract: 1 Role-play exercises with simulated patients may serve the purpose of training professionals to develop appropriate communication skills with adolescents. Authentic adolescent responses toward the physicians may be achieved by actors who themselves are in their teenage years. We describe our experience in continuing medical education programmes for primary care physicians aimed at improving their skills in communicating with adolescents, using simulation methodology with teenage actors. Eight 16±17-year-old a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…Conducting diagnostics and therapy with a sick child calls for a differentiated interactional approach at the parentphysician level. However, studies on communication training programs in the specialist area of pediatrics have mainly focused on patient-physician communication [5][6][7], and have largely neglected aspects of parent-physician communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting diagnostics and therapy with a sick child calls for a differentiated interactional approach at the parentphysician level. However, studies on communication training programs in the specialist area of pediatrics have mainly focused on patient-physician communication [5][6][7], and have largely neglected aspects of parent-physician communication.…”
Section: Introductionmentioning
confidence: 99%
“…They have proven to be highly realistic and to provide relevant feedback [8,10] resulting in improved objective structured clinical examination (OSCE) performance in undergraduate medical education [11]. In the field of pediatrics, children and adolescents have also served as standardized patients in communication training programs [5,6,[12][13][14][15] and in the context of performance evaluation (e.g. [16][17][18]).…”
Section: Introductionmentioning
confidence: 99%
“…This was contradictory to other studies. In one study adolescent SPs had more appreciation for clinicians with different viewpoints and doubts in various situations [15]. In another research project SPs reported a more balanced perspective on physicians [7].…”
Section: Discussionmentioning
confidence: 95%
“…This innovative approach addressed the need for well-trained simulated patients and helped to narrow an observable shortage of trained adolescents in that role. [3][4][5] Both the pharmacy and public high schools accomplished the goal of their individual mission statements for increasing collaborative educational efforts with one another. Prior to the fall of 2004, the role of simulated patient was most often filled by pharmacy faculty members and/or first-professional year students.…”
Section: -2mentioning
confidence: 99%
“…[12][13] The use of adolescent and pediatric simulated patients is rare among medical schools, but in instances where they have been thus employed, both students and faculty members have responded favorably regarding the benefits of such encounters. [3][4][5] This exercise is novel in that high school students with a theater course requirement were utilized to interact with pharmacy students in a professional patient encounter.…”
Section: -2mentioning
confidence: 99%